Exploring theme-based tasks using familiar topics in promoting secondary learners' speaking and writing skills - Maming, Khadijah; Yassi, Abdul Hakim; Saleh, Noer Jihad; Jubhari, Ria Rosdiana (Diksi, 2023)
This study attempted to explore theme-based tasks using familiar topics in promoting learners' productive skills namely speaking and writing skill at Indonesian secondary school context. This study was pre-experimental research undertaken in five junior secondary schools. There are eighty-six students participated as research respondents. Test and observation checklist used as research instruments. The research findings reported the mean scores on productive skills acquired by the students were getting improvement from pretest to posttest. In speaking skill, the mean score of posttest was 58.95 was better than 40.76 in pretest mean score. Similarly, the mean score of writing posttest was 76.85 was higher than 63.86 in pretest. It indicated that the progress of students' score in speaking skill was 18.19 and the progress of students' score in writing skill was 12.99. Although the gain scores in speaking and writing tests are slightly different, but it can be stated the students' productive skills promote significantly. Then, the result of t-test value on students' speaking skill posttest and pretest was 18.37, while the t-test value on students' writing skill posttest and pretest was 16.42. The both of these values are higher than t-table value. It indicated there is a significant difference between pretest and posttest for both tests. The students' English productive skills after treated by implementation of theme-based tasks were categorized as good achievement. Additionally, the majority of students' learning activities in English class are categorized as good category. They participated positively in English learning activities in terms of good attention, high seriousness, and activeness in group work.Keywords: Familiar Topics, Improvement, Productive Language, Theme-Based Tasks